2010
DOI: 10.5194/bg-7-2531-2010
|View full text |Cite
|
Sign up to set email alerts
|

Towards ground-truthing of spaceborne estimates of above-ground life biomass and leaf area index in tropical rain forests

Abstract: Abstract. The canopy height h of forests is a key variable which can be obtained using air-or spaceborne remote sensing techniques such as radar interferometry or LIDAR. If new allometric relationships between canopy height and the biomass stored in the vegetation can be established this would offer the possibility for a global monitoring of the above-ground carbon content on land. In the absence of adequate field data we use simulation results of a tropical rain forest growth model to propose what degree of i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…Statistical analysis has been a common method of fitting the biomass-height relationship. Widely used regression models include power [Chave et al, 2005;Köhler and Huth, 2010;Mitchard et al, 2011;Saatchi et al, 2011;Wang et al, 2013], linear [Fang et al, 2006;Skowronski et al, 2007], the quadratic polynomial [Lefsky et al, 2005b], and exponential functions [Yu et al, 2010]. Previous studies have shown that biomass-height relationships differ greatly across environmental gradients and among different forest types [Drake et al, 2003;Pan et al, 2004;Wang et al, 2013].…”
Section: Methods 221 Estimating Forest Stand Agementioning
confidence: 99%
“…Statistical analysis has been a common method of fitting the biomass-height relationship. Widely used regression models include power [Chave et al, 2005;Köhler and Huth, 2010;Mitchard et al, 2011;Saatchi et al, 2011;Wang et al, 2013], linear [Fang et al, 2006;Skowronski et al, 2007], the quadratic polynomial [Lefsky et al, 2005b], and exponential functions [Yu et al, 2010]. Previous studies have shown that biomass-height relationships differ greatly across environmental gradients and among different forest types [Drake et al, 2003;Pan et al, 2004;Wang et al, 2013].…”
Section: Methods 221 Estimating Forest Stand Agementioning
confidence: 99%
“…Normally, these methods can only be used at small spatial scales. Even when a greater number of trees is monitored, the risk of over-or underestimating the regional carbon balance due to heterogeneity in tropical forests (Köhler and Huth 2010) or other up scaling effects remains.…”
Section: Net Ecosystem Exchangementioning
confidence: 99%
“…The remote sensing component of the analysis 326 framework relies on lidar samplers and radar and passive optical imagers to sample and 327 map landscape vegetation spectral and spatial "metrics" at high spatial resolution (~25m). 328To relate the lidar and radar measures or "metrics" to in situ measures, lidar and radar 329 measures are then regressed against in situ timber height and volume measures in sample 330 plots (Kohler and Huth, 2010). The resulting regression equations are used to convert 331 landscape level lidar and radar metrics into regional, contiguous biomass and 3D 332 vegetation structure products.…”
mentioning
confidence: 99%
“…To relate the lidar and radar measures or "metrics" to in situ measures, lidar and radar 329 measures are then regressed against in situ timber height and volume measures in sample 330 plots (Kohler and Huth, 2010). The resulting regression equations are used to convert 331 landscape level lidar and radar metrics into regional, contiguous biomass and 3D 332 vegetation structure products.…”
mentioning
confidence: 99%